Magnetic gelatin-hesperidin microrobots promote proliferation and migration of dermal fibroblasts - Sun, Xuyan; Yang, Hua; Zhang, Han; Zhang, Weiwei; Liu, Chunyu; Wang, Xiaoxiao; Song, Wenping; Wang, Lin; Zhao, Qingsong (Frontiers in Chemistry, 2024)
Dermal fibroblasts play a crucial role in the formation of granulation tissue in skin wounds. Consequently, the differentiation, migration, and proliferation of dermal fibroblasts are considered key factors in the skin wound healing process. However, in patients with diabetic foot ulcers, the proliferation and migration of fibroblasts are impaired by reactive oxygen species and inflammatory factors impair. Therefore, a novel magnetic gelatin-hesperidin microrobots drug delivery system was developed using microfluidics. The morphology, motility characteristics, and drug release of the microrobot were assessed, along with its impact on the proliferation and migration of human dermal fibroblasts under high-glucose conditions. Subjected to a rotating magnetic field, the microrobots exhibit precise, controllable, and flexible autonomous motion, achieving a maximum speed of 9.237 μm/s. In vitro drug release experiments revealed that approximately 78% of the drug was released within 30 min. It was demonstrated through cellular experiments that the proliferation of human dermal fibroblasts was actively promoted by the nanorobot, the migration ability of fibroblasts in a high-glucose state was enhanced, and good biocompatibility was exhibited. Hence, our study may provide a novel drug delivery system with significant potential for promoting the healing of diabetic foot wounds.